THE EFFECT RICE HUSK ASH ON AVAIBILITY AND P UPTAKE OF CORN (Zea mays L.) ON ULTISOL - Wulan Maghfirah; Ilyas Ilyas; Yusnizar Yusnizar (Universitas Islam Negeri Ar-Raniry, 2024)
Ultisol can be used to plant food crops because the land spread is quite wide, but this must be done with proper soil and plant management (Prasetyo and Suriadikarta, 2006). One of the food crops that can be planted on this land is corn. According to the Central Statistics Agency (2018), Aceh's corn production in 2017 was 387,470 tons, while corn production in 2018 was 347,735 tons, which in this case experienced a decline. This research aims to determine the effect of rice husk ash on on soil chemical properties and P-uptake of corn plants (Zea mays L.) in Ultisol. The research used a non-factorial randomized block design (RAK), with 4 treatments and 5 replications so that there were 20 experimental units. The treatment composition was control, 10 t ha-1 rice husk ash, 20 t ha-1 rice husk ash, 30 t ha-1 rice husk ash. The parameters observed were soil chemical properties (pH, P-total of soil, and P-available of soil), oven dry weight of corn plants and P-uptake of corn plants. The parameters were measured at 45 days after planting (DAP). The results showed that rice husk ash had a significant effect on oven dry weight of corn plants, but the effect was not significant on soil chemical properties (pH, P-total of soil, and P-available of soil), and P-uptake of corn plants. Treatment with 20 t ha-1 of rice husk ash gave the best effect on the growth of corn plants.